Personal Nicknames of Zaplanje’s Small Town of Gadžin Han - Savić, Sandra G. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The paper analyzes the personal nicknames of Gadžin Han from a linguistic perspective. The personal nicknames are part of the anthroponomic system of Zaplanje, the geographic area to which the small town of Gadžin Han belongs. The research material, collected during the fieldwork from conversations with the town residents, includes 230 personal nicknames. It is categorized into two semantic groups: male personal nicknames (199) and female personal nicknames (31), and then further assigned to more specific semantic groups. For male nicknames, there are fifteen narrower semantic groups, and for female nicknames, there are six. The smaller number of female nicknames suggests a patriarchal culture within the community. The largest number of nicknames is motivated by family names and personal names of relatives, followed by occupation, as well as physical appearance. The index of nicknames, together with the reason given for the origin of the nickname, is also provided.